2019
DOI: 10.1021/acs.energyfuels.9b00043
|View full text |Cite
|
Sign up to set email alerts
|

Direct Assessment of Inhibitor and Solvent Effects on the Deposition Mechanism of Asphaltenes in a Brazilian Crude Oil

Abstract: The study of the asphaltene deposition mechanism is critical to understand and solve important problems in the petroleum industry. The same is valid for the selection of inhibitors to control or prevent asphaltene flocculation and/or deposition. However, most of the current information on these processes is obtained by experiments performed using model solvent systems. In the present study, we used quartz crystal microbalance (QCM) measurements as well as laser scanning confocal microscopy to characterize the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
(58 reference statements)
0
24
0
Order By: Relevance
“…In this sense, the proposition of molecules searches for structures that present acid-base interactions and/or involve steric stabilization. 20,21 Based on the selection of inhibition considering steric stabilization, as early as 1994 Chang and Fogler 15 indicated that the length and shape of the alkyl chain is very important for the additive efficiency, being similar steric interference for the aggregate growth.…”
Section: Phenomena Associated With Asphaltenes In Petroleum Exploratimentioning
confidence: 99%
See 4 more Smart Citations
“…In this sense, the proposition of molecules searches for structures that present acid-base interactions and/or involve steric stabilization. 20,21 Based on the selection of inhibition considering steric stabilization, as early as 1994 Chang and Fogler 15 indicated that the length and shape of the alkyl chain is very important for the additive efficiency, being similar steric interference for the aggregate growth.…”
Section: Phenomena Associated With Asphaltenes In Petroleum Exploratimentioning
confidence: 99%
“…58 In line with this observation, oil + inhibitor systems showed perturbations exclusively in submicron and micrometer size ranges through experiments conducted using a quartz crystal microbalance (QCM) and an analytical centrifuge (LUMiSizer). 21 As an example, results from the LUMiSizer showed that in case of precipitation, the inhibitor acts at the submicrometric scale, avoiding the stacking of nanoaggregates in even larger structures, thus reducing the size of objects by up to an order of magnitude. 21 This result indicates that probably the best starting point for the development of new inhibitors should be to assess the colloidal stability of nanoaggregates.…”
Section: R E L Eva N T ( E M P H a S I S O N R E C E N T ) Experimementioning
confidence: 99%
See 3 more Smart Citations